1982
DOI: 10.1073/pnas.79.12.3749
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c oxidase inhibition by anesthetics: thermodynamic analysis.

Abstract: The thermodynamic parameters that characterize the inhibition of cytochrome c oxidase activity, in rat liver submitochondrial particles, by n-butanol, tetracaine, and dibucaine were obtained. Three equilibria were assumed in order to account for the data: for the interaction of inhibitor with the native state of the enzyme, for the interaction of inhibitor with the thermally (reversibly) denatured state, and for the change between the native and thermally denatured states. Inhibition results from interaction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

1985
1985
1994
1994

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…The temperature dependence of cytochrome c oxidase catalyzed electron transport in each detergent that we tested agrees quite well with the previous studies that have been performed in phospholipid, detergent, or membrane environments, e.g., Smith & Newton (1968), Raison et al (1971) (1980). The largest apparent discrepancy between the present data and those that had been obtained earlier is the absence of a clear break in any of the Arrhenius plots of our data between 20 and 25 °C (refer to Figures 3 and 4) although some previous data also lacked a clear break (Denes & Stanacev, 1979;Yohsida et al, 1979;Vanderkooi & Chazotte, 1982). In each of our detergent systems, some curvature in the Arrhenius plot was evident, and two lines could have been drawn through the data that intersected between 20 and 25 °C.…”
Section: Discussioncontrasting
confidence: 90%
“…The temperature dependence of cytochrome c oxidase catalyzed electron transport in each detergent that we tested agrees quite well with the previous studies that have been performed in phospholipid, detergent, or membrane environments, e.g., Smith & Newton (1968), Raison et al (1971) (1980). The largest apparent discrepancy between the present data and those that had been obtained earlier is the absence of a clear break in any of the Arrhenius plots of our data between 20 and 25 °C (refer to Figures 3 and 4) although some previous data also lacked a clear break (Denes & Stanacev, 1979;Yohsida et al, 1979;Vanderkooi & Chazotte, 1982). In each of our detergent systems, some curvature in the Arrhenius plot was evident, and two lines could have been drawn through the data that intersected between 20 and 25 °C.…”
Section: Discussioncontrasting
confidence: 90%
“…They have shown that several enzymes, including cytochrome c oxidase, are inhibited by these local anesthetics. In analyzing thermodynamic parameters that characterize the interaction of anesthetics with cytochrome oxidase, they suggested that inhibition of enzyme activity was caused by a reversible perturbation of protein comformation, to a degree much smaller than that required for thermal denaturation (Vanderkooi & Chazotte, 1982). This suggests that an ethanol-induced increase in protein fluidity, in addition to specific binding near the metal sites in cytochrome oxidase, may cause changes that we observe in the -form of the enzyme.…”
Section: Discussionmentioning
confidence: 83%
“…Quinacrine (Casanovas et al, 1985a) was also observed to bind to cytochrome c oxidase. A variety of alcohols (butan-I -ol, pentan-I -ol, hexan-1 -ol and benzyl alcohol) as well as several amine local anaesthetics were observed to inhibit at multiple sites along the mitochondrial electron-transport chain, including the cytochrome c oxidase site (Chazotte & Vanderkooi, 1981;Vanderkooi & Chazotte, 1982). Six fully reduced flavin analogues have also been observed to bind to cytochrome c oxidase, with dissociation constants ranging from 5 to 8 ,UM (Ahmad et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Cytochrome c oxidase has been previously used as a model for drug-membrane enzyme interactions (Singer, 1980(Singer, , 1982Chazotte & Vanderkooi, 1981;Vanderkooi & Chazotte, 1982;Casanovas et al, 1983Casanovas et al, , 1985a. A variety of amine local anaesthetics (11 in all) with a significant range of lipophilicities (as measured by their octanol/water partition coefficients) demonstrated both competitive and mixed-type inhibition.…”
Section: Introductionmentioning
confidence: 99%